Impacts of STEM-integrated Cognitive Conflict-based Augmented Reality as a 21st Century Learning Strategy on Student Learning Motivation - Dwi Putri, Melisa; Mufit, Fatni; Hidayati, Hidayati; Riyasni, Selma (Universitas Negeri Padang, 2025)
Physics learning often faces challenges in terms of low student motivation, especially in abstract materials such as Newton’s law of gravity and Kepler’s law. Based on observations at SMAN 3 Batusangkar, it was found that student motivation was still in the moderate to low category, which had an impact on concept understanding and learning participation. To answer this problem, Augmented Reality (AR) based teaching materials based on STEM integrated cognitive conflict learning model were developed. This study aims to determine the effectiveness in increasing student learning motivation. Using pre-experimental method with One-Group Pretest-Posttest design, this study involved 30 students of class XI F3 as subjects. The research instrument was an ARCS model learning motivation questionnaire. The results showed a significant increase in student learning motivation from an average score of 2.50 to 3.84. The Wilcoxon test resulted in a significance of 0.000 (<0.05), which indicates the effectiveness of teaching materials in increasing student motivation. In conclusion, AR teaching materials based on cognitive conflict and STEM approach are effective in increasing learning motivation on Newton’s law of gravity material. This research is useful for the development of innovative learning media, improving the quality of the learning process, and as a reference for the development of technology-based media in science education.